Attachment Theory: Co-Regulation and the Social and Emotional Development of children from 0-5 years - Ní Chléirigh, Caoimhe (Trinity College (Dublin, Ireland). School of Education, 2022)
This study examines attachment theory and its relevance to early years settings. It argues that attachment theory has implications for the structure and management of early years settings and the training of its staff and management. It further considers how secure attachments promote the socio-emotional development of young children and how co-regulation and the use of emotion regulation strategies can promote socio-emotional learning (SEL). Various SEL programmes are evaluated. The implications for children with disabilities are considered and programmes promoting SEL for children with disabilities are examined, in particular DIR Floortime, which is considered a promising intervention both in the home and within early years settings. In light of the findings, suggestions are presented, including formally promoting SEL in Ireland, training staff and management in the Key Person approach, considering mixed-age groupings and improving pay and conditions in the early years sector.
Keywords: Early Intervention; Education